Analysis of High School History Grade XI Using Ernest Renan's Nationalism Approach - Prawira, Aditya; Maryati, Isa (HISTORIKA, 2019)
This article aimed to study how the state of Indonesian society before independence and after independence, which was explained by the high school history textbook by Sardiman by using the approach of Ernest Renan's nationalism theory. Ernest Renan, whether in the revised edition history textbook, has instilled the value of a united life will and whether in this history textbook also expresses the shared aspirations of the Indonesian people.